Investigation of complex refractive index of graphene oxide using polarisation response of graphene oxide-coated planarized optical waveguide / Gan Soon Xin - Gan , Soon Xin (2020)
Since a single atomic layer of carbon, also as known as graphene is being successfully exfoliated from 3D graphite, intense research on graphene and its derivative begins. Among them, graphene oxide (GO) is considered one of the most prominent candidates in the category of graphene derivatives for the application of electronic, optoelectronic and photonics. However, although GO has been applied in many applications like saturable absorbers of Q-switch laser and optical limiters for eye protection, its intrinsic optical properties especially complex refractive index reported so far still has a large deviation. Also, most of the optical characterization research on GO were conducted in the visible wavelength spectrum instead of near infrared (NIR) range. Thus, this thesis aims to determine the anisotropic complex refractive index of graphene oxide (GO) at 1550 nm using optical chip-based device. We propose a planarized optical waveguide structure that facilitates strong polarization dependent light interaction. The light propagation characteristic in thin film coated planarized optical waveguide is firstly studied. Using Finite Element Method (FEM), the optical response of planarized optical waveguide coated with thin film overlays with different refractive indices is obtained. The effective index, neff of optical waveguide increases with larger refractive index of the thin film overlay but decreases when its extinction coefficient is increased. The effective extinction coefficient, keff of the thin film coated increases when both the real and imaginary part of the thin film increases. It is found that TE-mode has stronger interaction with thin film overlay as compared to TM-mode, giving the capability of determining the optical constant of the thin film overlay by cross-referencing the experimental and numerical results. Following the completion of simulation work, experiment measuring the propagation loss-to-coating thickness profile of GO-coated planarized optical waveguide is carried out. GO films with sub-micron thickness (0.1 μm to 1.0 μm) were successfully produced using drop-casting technique. As predicted by simulation, the GO-coated waveguide exhibits large polarization dependent loss which depends strongly on the coating thickness. By cross-referencing the experimental and simulation results, the GO film’s complex refractive indices of 1.66+0.17i and 1.615+0.002i for TE- and TM-polarized light, respectively, are obtained. The uncertainties for the real part of refractive index are 0.03 and 0.020 for TE- and TM-polarized light respectively, whereas the uncertainties for the imaginary part of refractive index are 0.01 and 0.001 for TE- and TM-polarized light, respectively. The results obtained will be valuable in advancing the research and development of GO photonics, especially in the development of optical telecommunication devices where NIR wavelengths are used as information carrier.